Analysis of the Distribution of Zakat Infaq and Shadaqah (ZIS) to the Community in the Baznas of Tebing Tinggi City - Lisa Chintiya Tambunan; Muhammad Arif (Jurnal Fokus Manajemen, 2022)
The distribution of zakat is an activity carried out to accelerate and facilitate the distribution of zakat funds (including infaq and shadaqoh) from muzakki to mustahik. This makes zakat funds can be distributed according to what is intended and good and correct distribution will have the impact of reducing social inequality in society. The purpose of this study is to find out how the distribution of Zakat, Infaq, and Shadaqoh (ZIS) is and how it plays a role for the community in Baznas, Tebing Tinggi City. This study uses a qualitative approach. The results of this study are that the Tebing Tinggi City Baznas collects zakat maal, zakat fitrah, professional zakat, infaq, shadaqah, and so on assisted by the Zakat Collection Unit (UPZ) and directly from muzakki or through accounts with records of muzakki reporting zakat received will be submitted by filling out a signed deposit receipt and submitting it to the Tebing Tinggi City Baznas, in the case of zakat collection, muzakki also perform their own calculations of their zakat obligations and if needed the Tebing Tinggi City Baznas will help, and Tebing Tinggi City Baznas are required to provide proof of zakat deposit to every muzakki who has paid. Zakat, Infaq, and Sadaqah (ZIS) socialization activities are also very necessary and important to do. This can foster scientific insight about Zakat, Infaq, and Sadaqah (ZIS) for the community.